Industrial Service Flexibility and Regional Network Collaboration in Industrial Clusters - Ly, Pham Thi Minh; Lai, Wen-Hsiang (International Journal of Industrial Engineering: Theory, Applications and Practice, 2020)
<span style="font-family: 'Times New Roman','serif'; font-size: 12pt; mso-font-kerning: 26.0pt; mso-bidi-font-weight: bold; mso-fareast-font-family: 標楷體; mso-ansi-language: EN-US; mso-fareast-language: ZH-TW; mso-bidi-language: AR-SA;" lang="EN-US">Industry clusters link firms in specific industries in a geographical area and comprise vertical and horizontal business supply chain partners. Industrial service flexibility (ISF) is strongly related to goal-driven innovation within clusters in a regional network. The regional network collaboration (RNC) facilitates commerce and service relationships by coordinating production and merchandise flows. This study reviews relevant academic literature and divides the dimensions of ISF efficiency into “internal ISF” and “external ISF”. This study further explores the influential factors of RNC as dimensions of “geography”, “resource” and “network”. This study finds that the “distance proximity” and “company scale” are not significant to the efficiency of internal and external ISFs. “Talent resource” and “information network” provide significant linkages to the efficiency of internal and external ISFs. Finally, in order to improve the efficiency of ISF, “network information” is important to the internal ISF, and “network interaction” is an indispensable element in external ISF.